Estrutura da assembléia de cladóceros em reservatórios nos Estados de São Paulo e Paraná : riqueza, diversidade β e abundância. - Santos, Francini Vila dos (2005)
The main aim of this study was to evaluate the spatial and temporal patterns of richness, β diversity species and abundance, in six reservoirs located at Paraná State (Iraí, Parigot de Souza, Segredo, Mourão and Salto do Vau reservoirs) and São Paulo State (Rosana reservoir). We supposed that these attributes of the assemblage were higher in the transition region of the eutrophic reservoirs in the rain season. Cladocerans were sampled each three months, at subsurface, in mixing zone and in the deepest layer of water column, in three reservoir regions (fluvial, transition and lacustrine regions), from March to November 2002. Higher values of species richness were registered in the Mourão reservoir and lower values in the Salto do Vau reservoir (oligotrophics). There were no significant differences for species richness among the regions and hydrological periods. For b diversity, we found higher values in the Salto do Vau reservoir and lower values in the Segredo reservoir (mesotrophic). There was no a single pattern for β diversity according to the regions, but there was a temporal pattern that showed higher values in the dry season. The β diversity was significantly different among the reservoirs. The higher abundance was registered in Iraí and Parigot de Souza reservoirs (eutrophics). Significant differences were verified among the reservoirs according the trophic status. In general, the higher abundance was observed in the lentic regions of the reservoirs (transition and lacustrine regions). Temporally, we found significant differences between the periods, with higher values in the dry season. The results were different from the hypothesis. In general, we suggest that the cladoceran assemblage was structured according to the influence of the hydrodynamic and depth of the reservoirs to the richness and the β diversity, and according to the trophic status to the species dominance and abundance.